Climate Change and Crop Production - Reynolds, Matthew P (CABI, 2014)
In light of population growth and climate change, investment in agriculture is the only way to avert wide-scale food shortages or, in the worst-case scenario, catastrophic human suffering. Assuming investment is forthcoming, maintaining food security will require crop scientists to integrate and apply a broad range of strategies. These include tried and tested technologies such as conventional breeding and agronomy as well as new approaches such as molecular genetics and conservation agriculture. Each topic in this book has been selected for its potential contribution to maintain and increase crop productivity in unpredictable environments, providing readers with an overview of the state of the art in respective fields. Examples of successful applications as well as future prospects of how each discipline can be expected to evolve over the next 30 years are presented. The objectives of the book are twofold: (i) to lay out some basic concepts for crop scientists who, given changes in crop environments, may find it necessary to explore new disciplines in which they lack practical experience; and (ii) to provide an overview of the essential disciplines required for sustainable crop production for policy makers, academics and students of agriculture.